97.7k views
3 votes
I need help ASAP please (solving rational equations)

I need help ASAP please (solving rational equations)-example-1
User Kamokaze
by
5.4k points

1 Answer

3 votes


1 - (y-1)/(y) = (1)/(y^2 + 2y)


\frac y y - (y-1)/(y) = (1)/(y^2 + 2y)


(1)/(y) = (1)/(y^2 + 2y)


y = y^2 + 2y


y^2 + y = 0


y(y+1)=0


y = 0 \textrm{ or } y = -1

We rule out y=0 because of the denominator y in the original equation.

Answer: B: y=-1

User Polymeron
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.